Edukasi Penanggulangan Penyakit DBD di Panti Asuhan Harapan Kita - Sherli Shobur; Am. Al Fath Sabiliy Haq; Sukmawati Sukmawati; Aidil Dwi Rangga; Della Merry Puspita; Ade Lorensi Ilhamni; Jenny Sasmita Sari (Universitas Muhammadiyah Manado, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus, transmitted through the bite of the Aedes aegypti mosquito. This disease poses a serious public health problem in tropical and subtropical regions, including Indonesia, with an increased risk of transmission, especially during the rainy season. At the Harapan Kita Orphanage, unsanitary conditions, such as scattered trash and stagnant water, were found to be breeding grounds for mosquitoes, increasing the risk of DHF transmission among the children in the orphanage.To address this issue, a community service program was carried out with the aim of educating the children and caregivers at the orphanage about DHF prevention. Through interactive counseling sessions and the use of visual aids, it was hoped that the community would better understand the symptoms, modes of transmission, and proper preventive measures. The results of this program showed an increase in awareness regarding the importance of maintaining environmental cleanliness and the implementation of preventive measures, such as the use of abate powder and proper water management.